The Concept Of Multicultural Education In Islamic Education At Syafi'iyyah Pulo Air High School Sukabumi, West Java, Indonesia - Moh. Hifzul Muiz; Uus Ruswandi; Muhammad Erihadiana (Master of Islamic Studies Masters Program in the Postgraduate Institute of Islamic Studies Sultan Muhammad Syafiuddin Sambas, Indonesia, 2023)
The problem is that students and teachers have difficulty implementing multicultural education because they come from different cultural backgrounds from the provinces in Indonesia. Different languages and cultures are also daily habits. Haven't mastered the technology yet. computer. LCD and English and Arabic. Haven't memorized the Quran yet. The aim of the research is to find out the basic concept of multicultural education at As Syafi'yah Sukabumi High School, West Java. The methodology used is qualitative research. The results of the research are presented in a narrative, not statistical way. Data collection techniques using interviews, observation and documentation. Data analysis through data collection, then consulted with experts, concluded. . Research result the basic concept of multicultural education at SMA As Syafi'iyah Sukabumi West Java has been well implemented in accordance with the 45 Constitution and the 2013 Curriculum. Using the habituation and suritel methods and students are used to respecting others, respecting each other and preparing themselves for the future as human beings who must master science and technology. Able to use English and Arabic actively and passively, memorizing the Koran is a top program in schools. Multicultural applies mutual respect and respect for differences in language, ethnicity, culture, background.